Coercive Transnational Governance and Its Impact on the Settlement Process of Eritrean Refugees in Canada - Berhane, Aaron; Tyyskä, Vappu (Refuge: Canada's Journal on Refugees, 2017)
This article will examine the transnational practices of the Eritrean government, and their impact on the settlement of Eritrean refugees in Canada. The focus is on actions by the Eritrean regime that have a negative effect on refugees’ capacities for successful integration, and undermine Canadian sovereignty. The concept of coercive transnational governance (CTG) is introduced, to highlight this neglected aspect of refugee resettlement, with illustrations from 11 interviews, including eight Eritrean refugees, one Eritrean community activist, and two Canadian law enforcement officers, about the impact of CTG on Eritrean refugees’ lives.